Strategi Kreatif Program Shopee Liga 1 di Indosiar - Maria Erika Herawati; Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Television is an electronic media that has a function as a means of delivering messages to the audience. Television creates a wide variety of programs or events such as information or news, entertainment programs, educational programs, educational programs, and sports programs.Sports programs have a wide variety of types such as badminton, volleyball, basketball and football.As in this research that discusses the creative strategy of Shopee Liga 1 program that aired in Indosiar.In this program will be followed by as many as eighteen teams who will compete to win the title.In this study aims to find out the Creative Strategy of Shopee Liga 1 program in Indosiar.Then in this study using qualitative research method, using post positivism paradigm.Using Peter Pringle's program strategy concepts such as planning, organizing, directing and exerting influence, supervision.